Hybrid thermosensitive-mucoadhesive in situ forming gels for enhanced corneal wound healing effect of L-carnosine. (31st December 2022) - Fathalla, Zeinab; Mustafa, Wesam W.; Abdelkader, Hamdy; Moharram, Hossam; Sabry, Ahmed Mohamed; Alany, Raid G.
Abstract: Purpose: Thermosensitive in situ gels have been around for decades but only a few have been translated into ophthalmic pharmaceuticals. The aim of this study was to combine the thermo-gelling polymer poloxamer 407 and mucoadhesive polymers chitosan (CS) and methyl cellulose (MC) for developing effective and long-acting ophthalmic delivery systems for L-carnosine (a natural dipeptide drug) for corneal wound healing. Methods: The effect of different polymer combinations on parameters like gelation time and temperature, rheological properties, texture, spreading coefficients, mucoadhesion, conjunctival irritation potential, in vitro release, and ex vivo permeation were studied. Healing of corneal epithelium ulcers was investigated in a rabbit's eye model. Results: Both gelation time and temperature were significantly dependent on the concentrations of poloxamer 407 and additive polymers (chitosan and methyl cellulose), where it ranged from <10 s to several minutes. Mechanical properties investigated through texture analysis (hardness, adhesiveness, and cohesiveness) were dependent on composition. Promising spreading-ability, mucoadhesion, transcorneal permeation of L-carnosine, high ocular tolerability, and enhanced corneal epithelium wound healing were recorded for poloxamer 407/chitosan systems. Conclusion: In situ gelling systems comprising combinations of poloxamer-chitosan exhibited superior gelation time and temperature, mucoadhesion, and rheological characteristics suitable for effective long-acting drug delivery systems for corneal wounds.